Safeguarding the child and adolescent athlete - Lamb, M.; Kuhn, A. W.; LaBotz, M.; Diamond, A. B. (Current Sports Medicine Reports, 2018)
Youth athletics can provide numerous benefits to children. Until recently, athletics have been relatively free from scrutiny over the ways they put participants at risk. While it was often disregarded in early childhood research, athletics emerged as an avenue of child abuse in the 1980s. Individual cases reporting maltreatment of children participating in sports certainly existed, but these were felt to be single instances, not sentinel events. By the 1990s a small body of research had been established showing a pattern of abuse, spurring sporting organizations and governing bodies to assess their own policies and produce rough standards for safeguarding children against abuse. While multiple strides have been taken, there still exist gaps in knowledge surrounding abuse of child and adolescent athletes. This article reviews the scope and prevalence of abuse in youth athletics, definitions and what ultimately constitutes "abuse," the unique aspects of abuse in sport, and recognition and preventative efforts.